Pengaruh Price Earning Ratio dan Price Book Value Terhadap Harga Saham Pada Sub Sektor Semen yang Go Public di Bursa efek Indonesia - Pemy Christiaan; Rusdi Abdul Karim (AkMen JURNAL ILMIAH, 2021)
This study aims to determine how much influence is to determine how much influence Price Earning Ratio and Price Book Value simultaneously or partially on stock prices in the cement sub-sector. This research is a quantitative study, using ratio analysis. The analysis method uses multiple linear regression, the results show that the N Price Earning Ratio and Price Book Value simultaneously affect the Cement Sub-Sector Stock Price of 0.297 (29.7%), Partially Net Price Earning Ratio has a positive and insignificant effect on prices. Cement Sub-Sector Shares amounted to 0.188 (18.8%), the Price Book Value partially has a negative and significant effect on the Cement Sub-Sector Stock Price of -79.864 (-798.64%).